Life cycle reliability of RC bridge piers under seismic and aurborne chloride hazards. - Akiyama, Mitsuyoshi
Over the last two decades, the probabilistic assessment of reinforced concrete (RC) structures under seismic hazard has been developed rapidly. However, little attention has been devoted to the assessment of the seismic reliability of corroded structures. For the life cycle assessment of RC structures in a marine environmment and earthquake prone regions, the effect of corrosion due to airborne chlorides on the seismic capacity needs to be taken into consideration. Also, the effect of a type of corrosive environment on the seismic capacity of RC structures has to be quantified. In this paper, the evaluation of the displacement ductility capacity based on the buckling model of longitudinal rebars in corroded RC bridge piers is established, and a novel computational procedure to integrate the probabilistic hazard associated with airborne chlorides into life cycle seismic reliability assessment of these piers is proposed. The seismic demand depends on the results of seismic hazard assessment, whereas the deterioration of seismic capacity depends on the hazard associated with airborne chlorides. In an illustrative example, an RC bridge pier was modeled as single degree of freedom (SDOF). The longitudinal rebars buckling of this pier was considered as the sole limit state when estimating its failure probability. The findings show that the life cycle reliability of RC bridge piers depends on both the seismic and airborne chloride hazards, and that the cumulative time failure probabilities of RC bridge piers located in seismic zones can be dramatically affected by the effect of airborne chlorides.
Keywords: Reinforced concrete structures; Reliability; Seismic hazard; Airborne chloride; Hazard assessment; Rebar buckling